The effect of grain and pore sizes on the mechanical behavior of thin Al films deposited under different conditions. (1st April 2015) - Ben-David, E.; Landa, M.; Janovská, M.; Seiner, H.; Gutman, O.; Tepper-Faran, T.; Shilo, D.
Abstract: This paper presents a comprehensive study of the relationships between deposition conditions, microstructure and mechanical behavior in thin aluminum films commonly used in micro and nano-devices. A particular focus is placed on the effect of porosity, which is present in all thin films deposited by evaporation or sputtering techniques. The influences of the deposition temperature on the grain size, pore size and crystallographic texture were characterized by X-ray diffraction and scanning electron microscopy. The mechanical behavior of the films was investigated using four different methods. Each method is suitable for characterizing different properties and for testing the material at different length scales. Nanoindentation was used to study hardness at the level of individual grains; resonant ultrasound spectroscopy was used to measure the elastic moduli and porosity; and bulge and tensile tests were used to study released films under biaxial and uniaxial tensions. Our results demonstrate that even low porosities may have tremendous effects on the mechanical properties and that different methods allow the capture of different aspects of these effects. Therefore, a combination of several methods is required to obtain a comprehensive understanding of the mechanical behavior of a film. It is also shown that porosity with different pore size leads to very different effects on the mechanical behavior.